Cooling Media Treatments of the Welding Result of Aluminium 5083 using Gas Tungsten Arc Welding (GTAW) on Material Strengths - Bina Susila; Ali Azhar; Mark Jefferson; Achmad Syamsul H (Department of Marine Engineering, Institut Teknologi Sepuluh Nopember, 2026)
Cooling treatment will occur in every welding process. In welding construction of Aluminium raw materials using the Gas Tungsten Arc Welding (GTAW), sometimes carried out in different locations and conditions. The study aims to determine and analyses the treatment effect of variations cooling media using air, fresh water, and sea water on the material strength (tensile strength, bending strength and hardness) welding results of aluminium 5083. This research method is experimental by testing specimens of welding results. Data analysis with independent variables of air, fresh water, and sea water cooling media. The dependent variables are tensile strength, bending strength, intervening variable of hardness and as a control variable, Aluminium 5083 the same size of 300x150x6mm. The test results with air media cooling treatment obtained data, the direct cooling treatment the tensile test value was 193Mpa, the bending test was 61Kgf/mm2, the hardness test 63HRB, the media cooling treatment was flowed at a speed of 2,8m/s, the tensile test value was 178Mpa, the bending test was 49Kgf/mm2, the hardness test 55HRB and the media cooling treatment was flowed at a speed of 4,2m/s, the tensile test value was 157Mpa, the bending test was 55Kgf/mm2, the hardness test 59HRB.